Patent signal and financing constraints: a life cycle perspective and evidence from new energy industry - Li, Qianjie; Pang, Liyuan; Yin, Shi (Frontiers in Energy Research, 2023)
Based on the data of China’s new energy listed companies, this paper empirically studies the impact of the patent signal on the financing constraints of new energy enterprises and its mechanism. The results show that: (i) Both the invention patent application and the non-invention patent application can play a signaling role to alleviate the financing constraints of new energy enterprises; (ii) Analyst attention plays an intermediary role between the patent signal and the financing constraints of new energy enterprises. Compared with non-invention patents, analyst attention plays a more vital intermediary role on invention patents; (iii) Patent signal can alleviate the financing constraints of new energy enterprises in the growth and maturity stages by increasing analyst attention but has no apparent effect on the recession period; (iv) Compared with non-main board listed and small-scale new energy enterprises, patent signal has a more substantial effect on alleviating the financing constraints of main board listed and large-scale new energy enterprises.